Cooperação Intermunicipal no Brasil: os efeitos dos consórcios públicos de saúde à luz do Institutional Colletive Action - Nascimento, Alex Bruno Ferreira Marques do (2019)
Intermunicipal cooperation is a recurring theme in international literature and commonly used to analyze horizontal relationships in federated systems. In this sense, several partnership actions are signed in order to implement better public policies, or even in order to reduce transaction costs. Among these practices, a figure of public consortia in Brazil has been gaining notoriety since the 1990s, but especially after the Public Consortia Law of 2005, when legal certainty was provided to participating municipalities. The international literature has been devoted to analyzing the phenomenon of inter-municipal cooperation, among others, through the Collective Action approach, however, the focus has been on the inducers of cooperation or the dimensioning of transaction costs. Therefore, this phenomenon is characteristic of a study that presents as scale discounts in the regions of intercity cooperation. In this research the theoretical framework of collective action was used or elaborated, especially the theoretical framework addressed by Feiock (2007; 2013), called Institutional Collective Action (ICA), in order to estimate the collective results, but also to verify the relationship of contextual variables with the results of public policy. In Brazil, the phenomenon of public consortia was formed mainly in the environment and health sector, so, as a delimitation strategy, it opted for the health sector. Therefore, the following general objective was established: to verify the difference in collective results between the municipalities that decided to join a public health consortium in 2009/2010 and the municipalities that did not join public consortia by 2015. Therefore, it is , from a deductive, observational, longitudinal retrospective research using the statistical technique called “difference of differences”. After applying this technique, the results indicate that participation in the public health consortium improves the provision of health services, such as number of outpatient visits and number of medical appointments; and reduces the number of child mortality. Therefore, it can be inferred that long-distance cooperation generates benefits for participating municipalities and that the ICA contextual variables are relevant for observing the results of public policy.